Measurement of Anteroposterior diameters of normal brainstem by Magnetic Resonance Imaging - Singh, S.; Sharma, BR; Bhatta, M.; Poudel, N. (Journal of Gandaki Medical College-Nepal, 2019)
Aim: The aim of this study is to assess the anteroposterior diameter of brainstem (midbrain, pons and medulla) of normal Nepalese people to establish normal ranges and to correlate the measurement with patient’s age and gender. Method: The study is a cross-sectional prospective study which is performed in Gandaki Medical College, Pokhara. The data is collected over the period of 5 months from May 2018 to September 2018. The data of total 103 patients are collected who underwent (Magnetic Resonance Imaging) MRI head. Measurements of sagittal diameter at predefined levels i.e. distance between upper border of pons to midway between superior and inferior colliculi (A) for midbrain, distance between anterior surface of pons to the floor of fourth ventricle (B) for pons and anteroposterior diameter perpendicular to the long axis of medulla just above the posterior kink at cervicomedullary junction for medulla oblongata were made and noted. Result: The mean anteroposterior diameter of midbrain, pons and medulla oblongata was found to be 1.7048 ± 0.12 cm, 2.27 ± 0.13cm and 1.3 ± 0.088 cm respectively. The average ratio of sagittal diameter of pons to sagittal diameter of midbrain was 1.34 ± 0.099 cm and average ratio of sagittal diameter of pons to medulla oblongata was 1.75 ± 0.123 cm. Conclusion: There was no statistically significant correlation of the sagittal diameter of midbrain, pons and medulla with patient’s gender. The sagittal diameter of brainstem reached maximum at the age 20 and stopped increasing. The sagittal diameter of midbrain and medulla oblongata decreased slightly after the age of 50 and decreased significantly after the age of 70. There was no decrease in the sagittal diameter of pons after age.